Efectos de la variabilidad climática en diferentes densidades de siembra en el cultivo de maíz (Zea mays), amarillo duro variedad marginal 28-t en Cacatachi – Región San Martín - Tenazoa Fasanando, Dani (2007)
The present research work itself February Development -. June 2006, with the aim of assessing v "Effects of Climate Variability with different densities in growing corn (Zea mays) ': This experiment was conducted at the Fundo Cacatachi of UNSMs-T located in the Cacatachi district, province and department of San Martin, geographically LOCATED June 1 ° 25 'south latitude, 76 ° 00' west longitude, with an altitude of 328 msnmm was used the discoursed of (DBCR) defrauding 04 treatments and 03 Reps . Work consisted of the following activities: land preparation, planting with spacings of 80 x 20 cm. For T1, 80 x 40 cm. For T2, 80 x 60 cm. For T3 and 60 x 60 cm T4; desahíjes, weeding and hoeing Manual. It was fertilized with a dose rate of 120 A - 100 - 80 NPK. : In addition, data of temperature, precipitation and humidity were recorded, and the data of temperature and soil moisture announcement was also determined. The results show that the treatment Mayor grain yield (kg / ha) won T4 with 2, 47 MT / ha followed the T3 with 2, 15 TMha; T2 with 1.78 MT / ha and Ti 1, 65 MT / ha THIS adjusted to 14% moisture.